2014
DOI: 10.1002/jssc.201400129
|View full text |Cite
|
Sign up to set email alerts
|

Integrating qualitative and quantitative characterization of traditional Chinese medicine injection by high-performance liquid chromatography with diode array detection and tandem mass spectrometry

Abstract: The present study aims to describe and exemplify an integrated strategy of the combination of qualitative and quantitative characterization of a multicomponent mixture for the quality control of traditional Chinese medicine injections with the example of Danhong injection (DHI). The standardized chemical profile of DHI has been established based on liquid chromatography with diode array detection. High-performance liquid chromatography coupled with time-of-flight mass spectrometry and high-performance liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…Since DH launch in 2002, it has been widely used to prevent and treat ACS ( Yao et al, 2011 ). The main active ingredients of DH are flavonoids and phenolic compounds, for example, danshensu, salvianolic acid B, protocatechuic aldehyde, tanshinone IIA, rosmarinic acid and hydroxysafflor yellow A ( Xie et al, 2014 ; Wang et al, 2020 ). In addition, previous pharmacological studies have demonstrated that DH have the effects of antioxidant, anti-inflammatory, vasodilation and protect cardiac muscle due to its main pharmacological active components ( Wan et al, 2011 ; Jiang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since DH launch in 2002, it has been widely used to prevent and treat ACS ( Yao et al, 2011 ). The main active ingredients of DH are flavonoids and phenolic compounds, for example, danshensu, salvianolic acid B, protocatechuic aldehyde, tanshinone IIA, rosmarinic acid and hydroxysafflor yellow A ( Xie et al, 2014 ; Wang et al, 2020 ). In addition, previous pharmacological studies have demonstrated that DH have the effects of antioxidant, anti-inflammatory, vasodilation and protect cardiac muscle due to its main pharmacological active components ( Wan et al, 2011 ; Jiang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The calibration curves of four standards all showed good linearity at the concentration range (r 2 = 1 00). The limit of detection (LOD) and the limit of quantification (LOQ) were calculated based on the signal-to-noise ratios as 3 and 10, respectively [19,20]. The regression equation, LOD and LOQ of four standards (i.e., isoschaftoside, schaftoside, rutin, and isoquercitrin) were shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…To data LC-MS with reasonable qualitative and quantitative capability has been increasingly used for chemical profiling and QC of TCMs [6,10]. Among various LC platforms, ultra fast liquid chromatography (UFLC)…”
Section: Introductionmentioning
confidence: 99%